Factors influencing ecological sustainability in the ostrich industry in the Little Karoo, South Africa - Wheeler, Anita (Rhodes University, Faculty of Science, Botany Department, 2014)
The Little Karoo, situated in the Succulent Karoo biome of South Africa, has been heavily transformed by land use, and only 8.6% of the remaining natural vegetation is considered to be intact. There is ample evidence that the main cause of degradation is the overstocking of ostriches, an industry that has been the major economic driver of the area for more than 150 years. The ostrich stocking rate currently recommended is 22 ha.ostrichâ »Â¹. A literature review was used to examine the evidence, assumptions and rationale on which recommended and actually implemented stocking rates for ostriches are based. No experimental evidence using ostriches was found that supported the recommended stocking rate as either ecologically or economically sustainable. From the literature, there appears to be a wide gap between what are considered to be economically and ecologically sustainable stocking rates, with the implication that these two aims may be impossible to reconcile when practicing ostrich farming on natural veld. A comparison of recommended with actual stocking rates among land managers in the Little Karoo showed that all land managers far exceeded the recommended agricultural stocking rate of 22.8 ha.ostrichâ »Â¹. However, the stocking rates reported by land managers to the South African Ostrich Business Chamber were found to accurately reflect actual numbers determined when whole flocks had to be slaughtered after an outbreak of avian influenza. The recommended stocking rate appeared to be irrelevant to ostrich flock breeders and there appeared to be a trade-off between profitable ostrich farming and sustainable land-use practices. This study also investigated the attitudes and behaviour of ostrich farmers. It was found that environmental attitude is most likely the most important characteristic of a land manager to ensure positive conservation behaviour. This characteristic was most prominent in younger land managers with larger farms. The last component of the study integrated the context and complexity of the long term social, economic and ecological sustainability of this industry through the development of a logic model. The results showed a general lack of linkages between industry elements which impact on achieving sustainability targets. Greater collaboration between industry role-players, organized agriculture and conservation organizations is required to find a balance between utilization and conservation in the ostrich industry.
Keywords: Ostrich farms -- South Africa -- Little Karoo; Land degradation -- South Africa -- Little Karoo; Land use -- South Africa -- Little Karoo; Land degradation -- Environmental aspects -- South Africa -- Little Karoo; Conservation of natural resources -- South Africa -- Little Karoo; Sustainable development -- South Africa -- Little Karoo; Sustainable agriculture -- South Africa -- Little Karoo